Predictive mobility management using optiminized delays and security enhancement in IEEE 802.11 infrastructure networks - Biju, Issac (Universiti Malaysia Sarawak, UNIMAS, 2008)
The IEEE 802.11 wireless local area neyworks (also called WLAN) is very popular nowadays, and many public places have WLAN installations, for example in airports, coffee houses, shopping malls and customer service centers. Dealing with the mobility management and dealing with the security enhancement from the first and second part of this thesis respectively.